A caridade é, em tudo, a regra de proceder: análise do discurso espírita kardecista - Silva, Tamiris Vianna da [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
In this work, we analyze the Kardecist spiritist discourse, as it is currently circulating in Brazil, from the perspective of the Discourse Analysis of the French line, emphasizing reflections of Maingueneau (2008) on the notion of global semantics. From this point of view, discourse is considered as a system of semantic constraints which restricts all levels of speech (vocabulary, topics discussed, intertextuality, instances of enunciation) at the same time. This restriction system does not concern only verbal speech production but also makes it commensurable with the institutional network of the group that the enunciation of discourse presupposes and at the same time makes it possible. Thus, we analyzed the Kardecist spiritist discourse considering it as a discursive practice, in terms of Maingueneau (2008), in order to highlight the radical overlap between the verbal face and the social face of the discourse. For the development of the analysis, we organized a very diverse corpus, which includes different genres of verbal-visual nature, which does not cease to be a reflection of the diversity of production related to the spiritist speech. The guiding principle of analysis is the evaluation of the hypothesis formulated about this speech, that is, the trait/+Christianity/ is one of semantic features of its system of global semantic constraints. From our point of view, this trait does not exhaust the significance of the Kardecist spiritist discourse, but analysis reveals that it is present in both verbal face (according to the analysis we have developed over the ethos in the Kardecist spiritist discourse) and social face (according to the reflections on the present spiritist institutions) of this discourse, becoming thus one of the keys to its reading

Neste trabalho, analisamos o discurso espírita kardecista, tal como se encontra circulando atualmente no Brasil, a partir da perspectiva da Análise do Discurso de linha francesa, com ênfase nas reflexões de Maingueneau (2008) sobre a noção de semântica global. Desse ponto de vista, o discurso é considerado como sistema de restrições semânticas que restringe, ao mesmo tempo, todos os planos do discurso (vocabulário, temas tratados, intertextualidade, instâncias de enunciação). Esse sistema de restrições não só diz respeito à produção verbal do discurso, como também o torna comensurável com a rede institucional do grupo que a enunciação do discurso supõe e, ao mesmo tempo, torna possível. Assim, analisamos o discurso espírita kardecista considerando-o como uma prática discursiva, nos termos de Maingueneau (2008), com o intuito de evidenciar a imbricação radical que há entre a face verbal e a face social do discurso. Para o desenvolvimento da análise, organizamos um corpus bastante diversificado, que inclui diferentes gêneros de natureza verbo-visual, o que não deixa de ser um reflexo da própria diversidade da produção relacionada ao discurso espírita. O fio condutor da análise é a avaliação da hipótese que formulamos a respeito desse discurso, isto é, que o traço /+cristianismo/ é um dos traços semânticos de seu sistema de restrições semânticas globais. Do nosso ponto de vista, esse traço não esgota a “significância” do discurso espírita kardecista, mas a análise revela que está mesmo presente tanto na face verbal (conforme a análise que desenvolvemos sobre o ethos do discurso espírita kardecista), quanto na face social (conforme as reflexões que apresentamos sobre as instituições espíritas) desse discurso, constituindo-se, desse modo, como uma das chaves para a sua leitura
Keywords: Linguística; Análise linguística (Linguística); Análise do discurso; Religião na literatura; Ethos; Modalidade (Linguistica); Linguistic analysis (Linguistics); Brasil - Espiritismo na literatura